2015
DOI: 10.1017/cem.2014.60
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness and safety of a prehospital program of continuous positive airway pressure (CPAP) in an urban setting

Abstract: Background: Continuous positive airway pressure (CPAP) is commonly used in the treatment of acute cardiogenic pulmonary edema (ACPE) and acute exacerbations of chronic obstructive pulmonary disease (AECOPD). In-hospital evidence is robust: CPAP has been shown to improve respiratory status and to reduce intubation rates. There is less evidence on prehospital CPAP, although the emergency medical services (EMS) adoption of this modality is increasing. The objectives of this study were to 1) measure the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
(19 reference statements)
1
7
0
10
Order By: Relevance
“…Medical Services (EMS). [20][21][22][23][24] These studies are consistent with the ACUTE experience of submaximal CPAP adherence and difficult prehospital diagnosis, including treatment of patients with pneumothoraces. A recent systematic review identified 10 trials and quasi-randomised studies comparing prehospital NIV (including CPAP) with standard oxygen therapy.…”
Section: Open Accesssupporting
confidence: 63%
“…Medical Services (EMS). [20][21][22][23][24] These studies are consistent with the ACUTE experience of submaximal CPAP adherence and difficult prehospital diagnosis, including treatment of patients with pneumothoraces. A recent systematic review identified 10 trials and quasi-randomised studies comparing prehospital NIV (including CPAP) with standard oxygen therapy.…”
Section: Open Accesssupporting
confidence: 63%
“…The study protocols aimed at patients with presumed heart failure, COPD or asthma and the study patients’ initial oxygen saturation and respiratory rate were comparable to initial values in this study population. Transport time from departure from scene to arrival at emergency department was considerably shorter than in the present study, only 9.6 min [ 30 ]. Distance and transport time to hospital is an important factor when deciding how to treat patients with acute respiratory failure during ambulance transport; it is always a balance between time used to initiate a prehospital treatment and a faster arrival to definitive treatment at hospital.…”
Section: Discussionmentioning
confidence: 72%
“…Comparison of standard medical therapy plus CPAP to standard medical therapy alone has shown, that CPAP is superior when using SpO 2 or respiratory rate as outcome measures of effectiveness in patients with acute cardiopulmonary oedema or acute respiratory failure [ 10 , 12 , 17 ]. Two recent studies of prehospital patients with respiratory distress, conducted in North American urban settings, did not find any benefit of CPAP when comparing groups before and after implementation [ 30 , 31 ]. The study protocols aimed at patients with presumed heart failure, COPD or asthma and the study patients’ initial oxygen saturation and respiratory rate were comparable to initial values in this study population.…”
Section: Discussionmentioning
confidence: 99%
“…Prehospital non-invasive ventilation can be effective in treating acute exacerbation of COPD and cardiogenic pulmonary edema. Six studies [3,7,8,15,18,19] were reviewed for the effectiveness of prehospital or out-of-hospital use of CPAP for reducing mortality intubation rates and hospital stay length. Reducing endotracheal intubation rate in other ways helps in reducing the risk of ventilator-associated pneumonia, length of hospital stay, and mortality.…”
Section: Cpap V/s Bipap For Reducing Intubation Rates Mortality and Length Of Hospital Staymentioning
confidence: 99%
“…One systematic review [3], three randomized control trials [7,8,15], and two observational studies [18,19] were taken into account for review. A systematic review done by Bakke et al [3] showed a great decrease in intubation rates when CPAP is given in prehospital settings but no reduction in mortality and length of hospital stays.…”
Section: Cpap V/s Bipap For Reducing Intubation Rates Mortality and Length Of Hospital Staymentioning
confidence: 99%